2012
DOI: 10.1093/aje/kws171
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Mortality Study of Workers Exposed to Perfluorooctanoic Acid

Abstract: Perfluorooctanoic acid (PFOA) is persistent in the human body; the general population has serum levels of approximately 4 ng/mL. It causes tumors of the liver, pancreas, and testicles in rodents. The authors studied the mortality of 5,791 workers exposed to PFOA at a DuPont chemical plant in West Virginia, using a newly developed job exposure matrix based on serum data for 1,308 workers from 1979-2004. The estimated average serum PFOA level was 350 ng/mL. The authors used 2 referent groups: other DuPont worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 20 publications
4
139
3
1
Order By: Relevance
“…serum PFOA concentration 350 ng/mL; general population ~4 ng/nL) reported an increase of malignant and non-malignant renal diseases, but on limited numbers, and no exposure/response trend for diabetes or ischemic heart disease [278]. The most recent evaluation of mortality and cancer incidence in APFO production workers found no association between APFO exposure and risk of prostate and kidney cancer, diabetes and stroke [279].…”
Section: Occupationally Exposed Populationsmentioning
confidence: 99%
“…serum PFOA concentration 350 ng/mL; general population ~4 ng/nL) reported an increase of malignant and non-malignant renal diseases, but on limited numbers, and no exposure/response trend for diabetes or ischemic heart disease [278]. The most recent evaluation of mortality and cancer incidence in APFO production workers found no association between APFO exposure and risk of prostate and kidney cancer, diabetes and stroke [279].…”
Section: Occupationally Exposed Populationsmentioning
confidence: 99%
“…A cohort mortality study of the DuPont Washington Works (Parkersburg, West Virginia, USA) polytetrafluoroethylene (PTFE) plant, where APFO was used as a processing aid, reported chronic renal disease and kidney cancer associated with increasing occupational exposure to PFOA 12. Tetrafluoroethylene (TFE) exposure was highly correlated with PFOA exposure, and TFE is a kidney carcinogen in rats 13.…”
Section: Introductionmentioning
confidence: 99%
“…65-4.96). No trend was observed for any other autoimmune disease (Steenland and Woskie 2012). Dong et al (2013) reported a significant difference in serum levels of PFOA between children with (n = 231) (mean = 1.5 ± 1.3 ng/mL) or without (n = 225) (mean = 1.0 ± 1.1 ng/mL) asthma, and a significant dose-response relationship (AOR in quartile 4 [> 2.2 ng/mL] was 4.05, 95 % CI = 2.21-7.42).…”
mentioning
confidence: 82%
“…Data for PFNA, PFHxS and PFOS were also presented in the study (see Sections 8.3,16.3 and 18.3,respectively) (Power et al, 2013). Steenland and Woskie (2012) reported that cause-specific mortality in an occupationally exposed cohort of 1 308 workers, was significantly increased for mesothelioma (when compared with the US population). The overall SMR was 2.85 (95 % CI = 1.…”
mentioning
confidence: 99%